Accumulation of Cholesterol and Homocysteine in the Nigrostriatal Pathway of Brain Contributes to the Dopaminergic Neurodegeneration in Mice. (15th September 2018) - Paul, Rajib; Dutta, Ankumoni; Phukan, Banashree Chetia; Mazumder, Muhammed Khairujjaman; Justin-Thenmozhi, Arokiasamy; Manivasagam, Thamilarasan; Bhattacharya, Pallab; Borah, Anupom
Highlights: Nigrostriatal elevation of cholesterol & homocysteine in hypercholesterolemic (HCD) mice with hyperhomocysteinemia (HHcy). HHcy in HCD mice exacerbates motor abnormalities along with striatal dopamine loss. HCD in combination with HHcy causes significant loss of nigral dopamine containing neurons. Mitochondrial complex-I dysfunction with subsequent generation of hydroxyl radicals occurs in nigra of HCD + HHcy mice. The results point out the potentials of cholesterol and homocysteine toward the development of Parkinson's disease. Abstract: Elevated levels of cholesterol (hypercholesterolemia) and homocysteine (hyperhomocysteinemia, HHcy) in blood have been linked with the pathology of Parkinson's disease. However, the impact of their combined effect on brain is unknown. The present study aims to investigate the effect of HHcy on dopaminergic neurons in brain of mice with hypercholesterolemia. Mice were subjected to a high-cholesterol diet for 12 weeks to develop hypercholesterolemia, and were administered with homocysteine (250 mg/kg, b.w., i.p., 60 days) daily starting from 24th day of the high-cholesterol diet for induction of HHcy. The animals were subjected to Parkinsonian motor behavioral tests and sacrificed to estimate the levels of cholesterol, homocysteine and dopamine in brain, and to assess dopaminergic neuronal status. There occurred elevation in cholesterol and homocysteine levels in nigrostriatum of hypercholesterolemic animals with HHcy. Injection of homocysteine in hypercholesterolemic mice exacerbated the motor abnormalities as well as caused depletion of striatal dopamine level significantly, which was supported by a significant decrease in tyrosine hydroxylase (TH) immunoreactivity in striatum. While neither hypercholesterolemia nor HHcy caused significant changes in the number of TH-positive neurons, hypercholesterolemia in combination with HHcy resulted in a significant loss of nigral TH-positive neurons. The results highlighted the involvement of mitochondrial complex-I dysfunction with subsequent generation of hydroxyl radicals for the observed loss of midbrain dopamine neurons in animals receiving the combined treatment. Thus, the findings of the present study pointed out the combined effect of homocysteine and cholesterol toward dopamine neuronal dysfunctions, which has substantial relevance to Parkinson's disease.